2017
DOI: 10.1177/2321024917731840
|View full text |Cite
|
Sign up to set email alerts
|

Economic and Resource Impacts of Drip Method of Irrigation on Okra Cultivation

Abstract: Drip method of irrigation (DMI) introduced relatively recently in India has proved to save sizeable water and augment productivity of crops. Studies conducted mostly on high-value fruit crops have confirmed the various benefits of DMI. However, not many studies have brought out the economic and resource impacts of drip irrigation including its benefit-cost pattern using survey data in crops like okra (ladies' fingers) which is an important vegetable crop in India. In this article, we have made an attempt to fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 11 publications
1
7
0
Order By: Relevance
“…46.086/farm household over farmers in the control village. The findings are consistent with studies specifically in an Indian context [34,36,[74][75][76], which quantified the incremental benefits of climate smart technologies and study in Telangana (Nalgonda, Mahbubnagar and Warangal districts), which concluded that these technologies sustainably increase incomes and improve livelihoods [35,77]. Investment in agriculture was positively and significantly associated with farm incomes and a rupee investment in agriculture, increases the farm income by Rs.…”
Section: Determinants Of Farm Income Of Farmers During a Drought Yearsupporting
confidence: 87%
“…46.086/farm household over farmers in the control village. The findings are consistent with studies specifically in an Indian context [34,36,[74][75][76], which quantified the incremental benefits of climate smart technologies and study in Telangana (Nalgonda, Mahbubnagar and Warangal districts), which concluded that these technologies sustainably increase incomes and improve livelihoods [35,77]. Investment in agriculture was positively and significantly associated with farm incomes and a rupee investment in agriculture, increases the farm income by Rs.…”
Section: Determinants Of Farm Income Of Farmers During a Drought Yearsupporting
confidence: 87%
“…The informants affirmed the beneficiaries’ claims that the lack of technical know-how threatens the functionality of the system. Narayanamoorthy and Devika ( 2018 ) and Mudimu ( 2003 ) reiterated that smallholder farmers lack knowledge, training and appropriate managerial skills to manage some of the technologies. This leads to inefficiencies, wastage of resources and technical failures of the provided equipment.…”
Section: Results and Analysesmentioning
confidence: 99%
“…Developing irrigation schemes is a requirement for tackling household food insecurity in dry areas. Irrigation increases the capacity to produce food in severe drought conditions and expands possibilities for agriculture production and crop diversification (Narayanamoorthy & Devika 2018 ; ZimVAC 2018 ). Small-scale irrigation consisting of sprinkler/overhead irrigation, flood irrigation, furrow irrigation and drip irrigation systems has been identified as ideal for supplementing rain-fed agriculture and ensuring food security, especially in low-rainfall areas (Mango et al 2018 ; Riesgo et al 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…With 50% water application, the highest water use efficiency was acquired under polyethylene mulch. The impacts of economic and resource on drip irrigation including B/C manner using the survey data of okra cultivation have been studied in [20]. The study of the drip irrigation usage demonstrated that it can decrease nearly 15% of planting cost to save up to 47% of electrical energy and water quantity, and boost 49% of okra yield.…”
Section: Introductionmentioning
confidence: 99%